P80. Effects of deep brain stimulation on active and observational feedback learning in Parkinson's disease. Issue 8 (August 2015) - Meißner, S.N.; Südmeyer, M.; Keitel, A.; Pollok, B.; Bellebaum, C.
<x xml:space="preserve">Abstract</x> Decisions about how to respond optimally in daily life are often guided by learning from consequences of chosen actions. Response-outcome associations can be learned by active responding to a stimulus or by observing responses and associated consequences in others. There is evidence that, depending on medication status, patients with Parkinson's disease (PD) are relatively impaired in tasks requiring active learning from feedback. Regarding subthalamic nucleus (STN) deep brain stimulation (DBS), an increasingly utilized and highly effective treatment option for PD-symptoms, effects on learning are less clear. There are first indications of enhanced active feedback learning with STN stimulation due to a suggested modulatory effect of STN-DBS on the dorsal striatum, which is involved in linking own actions and outcomes. The aim of the present investigation was to compare the effect of DBS on active and observational feedback learning in patients with PD. Since learning by observation may depend less on the dorsal striatum, we hypothesized that STN stimulation affects learning of associations during active but not observational feedback learning. Twenty PD patients with STN-DBS and 20 age-matched controls performed active and observational feedback learning tasks. PD patients, remaining on their regular dopaminergic medication, completed both tasks ON and OFF-stimulation. During the active learning task, subjects had to respond to abstract visual stimuli with either the left or the right hand by button press. After each response, they received positive or negative feedback. During the observational learning task, subjects observed responses and accompanying outcomes of another person. Test phases consisting of trials without feedback served to assess learning of stimulus–response-outcome associations. We will present preliminary results regarding the effects of STN-DBS on observational and active feedback learning in PD patients. The findings will be discussed in light of the need to further understand not only motor but also cognitive effects of DBS in PD patients.